Impresi Brand Image, Brand Awareness, dan Relationship Marketing terhadap Customer Loyalty Produk (Studi Kasus Customer Kosmetik Wardah di Outlet Ana Beauty Demak) - Lailatus Saadah; Adhitya Yoga Prasetya (JURNAL ILMIAH EDUNOMIKA, 2025)
This research was conducted to identify how the influence of brand image, brand awareness, and relational marketing on customer loyalty. The research took place at Ana Demak Outlet involving 100 respondents. These respondents are customers of Wardah products. The data collection technique in this study used a questionnaire. This research method is quantitative, which includes: validity test, heteroscedasticity test, multicollinearity test, multiple linear regression test, T test, F test, and coefficient of determination (R2) test with SPSS application. Keywords: Brand Image, Brand Awareness, Relational Marketing, Customer Loyalty.